Effect of Seasonal Variation on Chemical Composition and Physicochemical Properties of Hedychium spicatum Rhizomes Essential Oil. Issue 6 (2nd November 2019) - Bhardwaj, Sapna; Rashmi,; Parcha, Versha
Abstract: Effectiveness of medicinal plants dependents upon chemical composition and amount of active constituents that present in the species, which may be highly influenced by different factors such as, growing conditions, seasons, climatic conditions, sun light exposure and altitude etc. Therefore the present work aims to study the effect of different seasons on physicochemical profile of Hedychium spicatum rhizomes essential oil from Uttarakhand. The yield (%) of H. spicatum rhizomes essential oil was varying from 1.16 ± 0.012 % to 1.64 ± 0.018 % on moisture free basis. Seasonal variation in chemical composition of H. spicatum essential oil obtained in different seasons was determined by GC/MS analysis and total 65 peaks were identified. 1, 8-cineole, α-cadinol, α-elemol and τ-muurolol were present in essential oil samples collected in different seasons. The major chemical compounds of H. spicatum essential oil in rainy and summer seasons were 1, 8-cineole (21.18 % and 21.81 %) and α-cadinol (18.43 % and 17.49 %). While α-elemol (16.44 %) and α-cadinol (15.99 %) were found major compounds in autumn season. The main compounds of winter were α-cadinol (18.79 %) and 1, 8-cineole (14.83 %). Results of GC/MS and physicochemical analysis revealed that, different seasons affect chemical composition and physicochemical properties viz. yield (%), saponification value, acid value, ester value and glycerol content significantly.